Misalignment of policy priorities and financing for early childhood education: Evidence from Ethiopia, Liberia, and Mainland Tanzania. (2022) - Kim, Janice; Robinson, Natasha; Härmä, Joanna; Jeffery, David; Rose, Pauline; Woldehanna, Tassew
Highlights: A novel approach to comparing ECE financing systems across Ethiopia, Liberia, and Mainland Tanzania. While ECE is a policy priority in these three countries, this commitment is not aligned with the allocation of funding. Moreover, government, schools, and households are not aligned on which children should be prioritised for ECE. This has led to more children being enrolled than planned for by government, further exacerbated underfunding. Systems based approach can help to anticipate outcomes of ECE underfunding. Abstract: This article assesses the financing of early childhood education (ECE) in three resource-constrained contexts: Ethiopia, Liberia, and Mainland Tanzania. Based on an analysis of policy documents and education administrative data, as well as surveys with key policymakers, school principals, and parents, it identifies that ECE is seen as a national priority in government policies across the three countries. However, this commitment is not aligned with the allocation of sufficient financial resources by each of the governments, which are extremely low in all three countries. This misalignment is associated with inequitable resource allocation, further reinforcing gaps in access to quality ECE between more advantaged and disadvantaged populations within the countries.